The Use Of Cronbach Alpha Reliability Estimate In Research Among Students In Public Universities In Ghana. - Frank Quansah (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2017)
This study examines the use of Cronbach alpha reliability estimate in research among university students in Ghana. An exploratory research design was employed in the study. University students' (both undergraduate and post-graduate) research works were selected from three public universities in Ghana. With the use of inclusion criteria, purposive sampling technique was used to sample 100 research works conducted by students. The sampled research works were examined to evaluate how the students used Cronbach alpha reliability estimate. It was revealed that 91% of the works properly satisfied the conditions for the use of Cronbach alpha. However, 81% of the students calculated for the alpha for multiple constructs which suggests that alpha was treated as a measure of multidimensionality instead of internal consistency. It is recommended that applied courses in research and statistics should be mounted in the various public universities in Ghana. Workshops and seminars should also be organized for both students and lecturers on the use of Cronbach alpha reliability estimate.